‘If only someone had told me…’: A review of the care of patients dying in hospital - Edmonds, Polly (Clin Med (Lond), 2003)
Approximately half of all patients who die do so in hospital. Despite the advent of palliative care in the UK, there is evidence that the care that many patients receive in the final phase of their illness in hospital is poor. Building on a study of bereaved relatives' views of the information provided by an inner city hospital trust during an admission in which a patient died, this article explores the factors that may contribute to sub-optimal care for patients dying in hospital. In particular, a lack of open communication, difficulties in accurate prognostication and a lack of planning of end-of-life care can all result in poor care. Strategies to improve care, such as the use of integrated care pathways, advance directives and education initiatives, are discussed.